Analisis Faktor Faktor Yang Mempengaruhi Audit Delay Di Kabupaten/Kota Provinsi Sumatra Selatan Tahun 2016-2020 - Shelly Krisandri; Maria Maria; Anggeraini Oktarida (Journal of Economic, Bussines and Accounting (COSTING), 2023)
In the districts and municipalities of South Sumatra, this study seeks to ascertain the size of local governments, audit findings, audit opinions, leverage, and the degree to which regional finances depend on audit delays. 17 counties and cities in South Sumatra make up the study's population. 85 saturated samples from 17 districts and municipalities in South Sumatra were collected over a 5-year period and used in the study. Using document technology, data collection methods. Multiple linear regression analysis was conducted in this study using SPSS version 25. According to the findings of partial and concurrent investigations, regional government size (X1), audit findings (X2), audit opinion (X3), leverage (X4), and regional-level financial reliance (X5) had negligible or no effects on audit delays. Keyword: Audit Delay, Size of Government, Audit Findings, Audit Opinion, Leverage, and level of regional Financial Dependences